Integrating Attachment Theory to Support a Client Coming to Terms with Infidelity - Claire, Carolyn A. (Canadian Journal of Counselling and Psychotherapy, 2010)
Finding it difficult to overcome the emotional distress experienced when considering her husband’s infidelity, a client seeks counselling support. The client’s goal was to learn about herself and to use the experience as an opportunity for self transformation. The case study utilizes Attachment Theory and Cognitive Behavioural Therapy to help the client develop self-awareness and come to terms with the experience.